1990
DOI: 10.1111/j.1365-2621.1990.tb05189.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and Chemical Characteristics of Fresh Pork Roasts Cooked to Different Endpoint Temperatures

Abstract: Pork roasts cooked to various endpoint temperatures were evaluated by sensory and chemical analyses. Increased endpoint temperatures were associated with increased cooking losses; decreased juiciness, pink color, and metallic flavor; increased graininess, brown color, and pork flavor. Increased endpoint temperatures also led to a concentration of lipid, protein and certain fatty acids. Cholesterol levels were not significantly influenced by endpoint temperature. Lipid content was decreased by removal of extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(53 citation statements)
references
References 16 publications
9
43
0
1
Order By: Relevance
“…Taking into consideration the eating quality parameters tenderness, juiciness, flavour and abnormal flavour, Wood, Nute, Fyrsey, and Cuthbertson (1995) recommended a core temperature of 72.5°C as ideal for grilled chops and 75 to 80°C for roast pork. The latter contrasts the earlier recommendations of Heymann, Hedrick, Karrasch, Eggeman, and Ellersieck (1990) of at least 71.1°C and no more than 76.6°C as the end point temperature for fresh pork roasts founded on minimising pink colour in some muscles and maximising other sensory characteristics and yield of cooked meat. In the present study, the core meat temperature of 72°C was chosen as a compromise of suggested optimal temperatures for roasting and grilling.…”
Section: Discussionmentioning
confidence: 72%
“…Taking into consideration the eating quality parameters tenderness, juiciness, flavour and abnormal flavour, Wood, Nute, Fyrsey, and Cuthbertson (1995) recommended a core temperature of 72.5°C as ideal for grilled chops and 75 to 80°C for roast pork. The latter contrasts the earlier recommendations of Heymann, Hedrick, Karrasch, Eggeman, and Ellersieck (1990) of at least 71.1°C and no more than 76.6°C as the end point temperature for fresh pork roasts founded on minimising pink colour in some muscles and maximising other sensory characteristics and yield of cooked meat. In the present study, the core meat temperature of 72°C was chosen as a compromise of suggested optimal temperatures for roasting and grilling.…”
Section: Discussionmentioning
confidence: 72%
“…However, the main part of cooking loss is water (Heymann et al . ). The water is probably lost due to heat‐induced protein denaturation during cooking of the meat, which causes less water to be entrapped within the protein structures held by capillary forces.…”
Section: Resultsmentioning
confidence: 87%
“…Moisture in meat is mainly retained by capillary force between myofibrils, but it was partially expelled during cooking due to heat‐induced protein denaturation, resulting in a decrease in moisture percentage in all cooking groups (Heymann et al . ; Toldrá ). SIH showed the highest percentage of lipid ( P < 0.05) and the other three cooked groups did not differ ( P > 0.05).…”
Section: Resultsmentioning
confidence: 99%